Clay minerals and Sr-Nd isotopic composition of the Bay of Bengal sediments: Implications for sediment provenance and climate control since 40 ka. (10th November 2018) - Li, Jingrui; Liu, Shengfa; Shi, Xuefa; Zhang, Hui; Fang, Xisheng; Chen, Min-Te; Cao, Peng; Sun, Xingquan; Ye, Wenxing; Wu, Kaikai; Khokiattiwong, Somkiat; Kornkanitnan, Narumol
Abstract: Grain size, clay mineralogy, 87 Sr/ 86 Sr, εNd, and AMS 14 C analyses of deep-sea sediments cored in the central Bay of Bengal are used to reconstruct the evolution of provenances and climate control since the last glacial period. Clay minerals, 87 Sr/ 86 Sr ratios and εNd values indicate a mixture of sediment from the Himalaya source, Indian Peninsula and Indo-Burman Ranges/Irrawaddy River. These analyses show that the Himalaya Mountains and Indo-Burman Ranges/Irrawaddy River are the main suppliers before the Holocene period, while the inputs of erosion materials from the Indo-Gangetic floodplain and the Indian Peninsula increase during the Holocene period, accompanied by reduced inputs of the Indo-Burman Ranges and Irrawaddy sediments. The regional "source-sink" process is significantly controlled by the climate. Warm and wet climate conditions and enhanced Indian monsoon intensity during the Holocene period are responsible for the increase of sediment input from the Indo-Gangetic Plain and the Indian Peninsula by improving erosion in the source area, input from the floodplain to the river channel and the intensity of the southwest monsoon current. In contrast, due to the decrease of the northeast monsoon current during the Holocene period, sediment input from the Irrawaddy and Indo-Burman Ranges are constrained. Deposition center transition between the submarine fan and shelf during the last glacial period and the Holocene period occurs in response to the sea level change, which controls the sedimentary mode and thus significantly influences the transportation and deposition processes in the Bay of Bengal (BoB).